Investigating the Performance of Solar Steam Generation Using a Carbonized Cotton-Based Evaporator - Chen, Haoming; Chen, Yuchao; Zang, Jinqi; Sha, Changchang; Xiao, Yupeng; Wang, Wenju; Wang, Haihou; Wu, Juai (Frontiers in Energy Research, 2022)
Solar-driven steam generation as a potential green technology has attracted extensive attention to solve freshwater scarcity crisis. Photothermal materials prepared by many strategies have been widely reported. However, there is still a challenge to develop an easily prepared, environmental-friendly and low-cost material to drive solar steam generation. Herein, a simple, scalable and porous carbonized cotton biomass was prepared as evaporator to enhance solar evaporation. Carbonized cotton biomass is a black material with excellent light absorption ability in the range of full spectral solar radiation (300-2500 nm). In this work, Cotton is carbonized by flat plate heating. The flat plate heating carbonization method is much shorter than that of the conventional carbonization method, and the equipment does not need to clean, almost no by-products. Compared with cotton carbonized in tubular furnace, flat plate heating carbonization can be used to prepare larger scale and lower cost solar thermal conversion materials without reducing the steam generation rate (0.78 kg∙m-2∙h-1, 1kW∙m-2) and photothermal conversion performance. In addition, carbonized cotton as an evaporator heated up rapidly under 1sun irradiation and reached a stable temperature in 20 seconds, greatly improving the photothermal conversion rate. This work would provide a new strategy for simplifying the production of biomass thermal evaporators.